(untitled) (Castilla. Estudios de Literatura, 2016)
The aim of this article is to investigate how Enrique Vila-Matas used the technique of autofiction, in El mal de Montano (2002). This work seems extraordinarily interesting to approach the keen problem concerning relationships, definitions, and classifications between autofiction and parody in order to enjoy the network of intertextual relations which El mal de Montano wonderfully presents.